The role of active forms of oxygen in the apoptosis mechanisms in case of experimental injury of the cornea and the ways of its correction - Nesteruk, S. V.; Klishch, I. M. (Journal of Education, Health and Sport, 2017)
<span style="font-size: 12pt; font-family: 'Times New Roman', serif; background-image: initial; background-position: initial; background-size: initial; background-repeat: initial; background-attachment: initial; background-origin: initial; background-clip: initial;" lang="UK">The purpose of our study was to find out the peculiarities of the corrective effect of a drug created on the basis of biological raw material - a concentrate of a deproteinized thermal layer of pig skin, on<span style="font-size: 12pt; font-family: 'Times New Roman', serif; background-image: initial; background-position: initial; background-size: initial; background-repeat: initial; background-attachment: initial; background-origin: initial; background-clip: initial;" lang="EN-US"> the free oxygen radicals level and<span style="font-size: 12pt; font-family: 'Times New Roman', serif; background-image: initial; background-position: initial; background-size: initial; background-repeat: initial; background-attachment: initial; background-origin: initial; background-clip: initial;" lang="UK"> apoptotic death of blood cells in an experimental mechanical non-penetrating corneal trauma. <span style="font-size: 12pt; font-family: 'Times New Roman', serif; background-image: initial; background-position: initial; background-size: initial; background-repeat: initial; background-attachment: initial; background-origin: initial; background-clip: initial;" lang="EN-US">During the<span style="font-size: 12pt; font-family: 'Times New Roman', serif; background-image: initial; background-position: initial; background-size: initial; background-repeat: initial; background-attachment: initial; background-origin: initial; background-clip: initial;" lang="UK"> non-penetrating mechanical corneal injury, intensification of free radical processes (increase of AFK levels up to 14 days by 200.5%) and growth of spontaneous apoptosis (138.9% after 14 days of the experiment) were determined. <span style="font-size: 12pt; font-family: 'Times New Roman', serif; background-image: initial; background-position: initial; background-size: initial; background-repeat: initial; background-attachment: initial; background-origin: initial; background-clip: initial;" lang="UK">The application of drops to the eyes "Efial" and eye gel "Solcoseril"<span style="font-size: 12pt; font-family: 'Times New Roman', serif; background-image: initial; background-position: initial; background-size: initial; background-repeat: initial; background-attachment: initial; background-origin: initial; background-clip: initial;" lang="EN-US"> to animals with <span style="font-size: 12pt; font-family: 'Times New Roman', serif; background-image: initial; background-position: initial; background-size: initial; background-repeat: initial; background-attachment: initial; background-origin: initial; background-clip: initial;" lang="UK">mechanical injury to the cornea had a positive effect on the indicators of active forms of oxygen and spontaneous apoptosis from the 3rd day of the experiment. Correction with the concentrate of the deproteinized heat layer of the pig's skin is probably more effective with respect to the action of the reference preparation of deproteinized hemoderivate from the blood of calves, especially after 10 days of the experiment. <span style="font-size: 12pt; font-family: 'Times New Roman', serif; background-image: initial; background-position: initial; background-size: initial; background-repeat: initial; background-attachment: initial; background-origin: initial; background-clip: initial;" lang="UK">Our data indicate that in the experimental non-penetrative mechanical trauma of the cornea, mitochondria play an important role in the implementation of cell death due to hyperproduction of active forms of oxygen, while one of the ways of initiation of apoptosis is mitochondria-mediated.